Floristic diversity of plant communities in sandy wadis of the northern Algerian Sahara (Ghardaïa region) - Widad, Merchela; Bouallala, M’hammed; Bradai, Lyés; Souddi, Mohammed (Biodiversity: Research and Conservation, 2023)
Plant species diversity was studied in 20 sandy wadis of the northern Algerian Sahara (Ghardaïa region). Based on subjective sampling, 20 floristic surveys were carried out in the various sandy biotopes in February-April 2022. Through an ascending hierarchical analysis, we distinguished 3 phytoecological groups and assessed their functional, biogeographic, and abundance characteristics. The recorded plants represented 15 species (296 individuals) belonging to 15 genera of 10 botanical families. The most represented families were the Fabaceae, Anacardiaceae, Brassicaceae, and Poaceae. In terms of the real plant-life spectrum, hemicryptophytes (51.7% of individuals) dominated the sandy wadis, followed by chamaephytes (33.1%) and phanerophytes (15.2%). In the real dispersal spectrum, the barochores prevailed (60%). The real phytogeographic spectrum shows that the Saharan endemic element reached the highest share (32.7%). In terms of abundance, an analysis of the real spectrum revealed that very common species (52%) dominate in the Ghardaïa region, but some fairly rare plants were also found. Indeed, the sandy biotopes of the wadis of the Ghardaïa region are valuable habitats for the conservation of plant species in the northern Algerian Sahara.